Story-based Interactive Educational Learning Design to Improve the Reading Skills of Third-Grade Elementary School Students - Hanina Hanina; Tuti Herawati; Anita Purba (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2023)
Students' cognitive abilities certainly vary, some are quick to grasp lessons and some are slow. Sometimes the learning process can also take place conducive but not infrequently the learning class tends to be crowded, boisterous, and some students seem lazy, or even cool with drawing activities. The purpose of this study was to describe the improvement of reading skills of third-grade students of SDN 010051 Hessa Air Genting after using a story-based interactive educational learning design. This research method is qualitative with data collection techniques through observation, interviews, and documentation. Data analysis techniques follow the stages of Miles and Huberman's analysis, namely data reduction, data presentation, and verification. The results showed that the story-based educational, interactive learning design by utilizing a variety of colored and illustrated storybooks in the library, as well as providing opportunities to read with the sonorous method can spur the interest and reading ability of grade III students at SDN 010051 Hessa Air Genting. It can be recommended that if teachers want to improve students' reading skills, then they can use this learning design as an alternative to teaching and learning in the classroom.